2012
DOI: 10.1016/j.ijsu.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of oncoplastic techniques in the surgical management of locally advanced breast cancer

Abstract: Oncoplastic surgical techniques for selected patients decrease the rates of radical surgery despite large tumors. (www.clinicaltrials.gov, NCT00820690).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Skin sparing mastectomy (SSM) and/or nipple sparing mastectomy (NSM) are popular in some of the LABC cases because of advantages of better local control, esthetic and satisfaction results [13,29]. In OBCS, by the use of otology tissues for reconstruction, implant problems are avoided [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin sparing mastectomy (SSM) and/or nipple sparing mastectomy (NSM) are popular in some of the LABC cases because of advantages of better local control, esthetic and satisfaction results [13,29]. In OBCS, by the use of otology tissues for reconstruction, implant problems are avoided [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this approach provides a better quality of life than applications performed at later stages [11,12]. Additionally, oncoplastic techniques can increase the rate of BCS in cases of LABC [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Mathes et al [18] operated 17 patient with LABC utilizing advanced oncoplastic techniques with no positive margins, Similary Viera et al [16] reported margin length 16.44 mm by oncoplastic surgery with no positive margins, Emiroglu et al [14] found that the mean surgical margin length was 8.7 mm (range 5 -17 mm) with positive margins in 7.1% of cases, in a study done by Clough et al [21] patients who received NACT and OS had a positive margins rate 10.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the wider margins enabled by OBS results in lower incidence of locoregional recurrence remains to be seen on a longer follow-up. Other studies with longer follow-up have indicated a recurrence rates of 6-10 % following OBS which is comparable to that of conventional BCS [20,21]. The study may be criticized on the aspect that it is not a prospective, randomized study; rather, it relies on comparing OBS with a retrospective cohort.…”
Section: Discussionmentioning
confidence: 99%